Love And Wisdom In Some Major World Religions: Judaism, Christianity, Islam, Hinduism And Buddhism - June McDaniel (IAHN-TP Palangka Raya, 2022)
Love and wisdom are important in all of the religious traditions we have observed, though they are interpreted differently. All people seek to live a good life, and the way that this can be known is through their religion’s moral and intellectual goals. In the Western monotheistic traditions, the love that is shown towards other human beings is understood to be ultimately God’s love, and the best thing that people can do for each other is to show and share that love. One loves for the sake of God, and because that love is the most important thing one can share. Love is not passive, but rather active, involved in charity and helping others.